Islamic Local Wisdom Scholarship: Core Themes and Emerging Research Directions from a Bibliometric Perspective - Purnama, Erlangga Wanda; Muthoifin, Muthoifin (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to provide the first comprehensive bibliometric mapping of Islamic local wisdom research to identify publication trends, intellectual structures, thematic evolution, and future research directions within this emerging field. Methodology: Using a bibliometric approach, data were retrieved from the Scopus database on 9 December 2025, resulting in 191 English-language journal articles published between 2009 and 2026, which were analyzed using Biblioshiny, Microsoft Excel, and VOSviewer. The analysis examined publication growth, leading authors, institutions, journals, citation patterns, and keyword co occurrence networks. Results: This study contributes original value by conceptualizing Islamic local wisdom as a dynamic and integrative epistemological framework rather than a static cultural construct, offering both theoretical insights and practical implications for education, law, social cohesion, and policy development, while providing a structured agenda for future interdisciplinary and comparative research.